Lernwerkstätten an Hochschulen Orte einer inklusiven Pädagogik - Schmude, Corinna; Wedekind, Hartmut (Lernen und Studieren in Lernwerkstätten. Impulse für Theorie und Praxis, 2016)
The second volume of the series "Learning and studying in learning workshops" discusses how inclusion can be thematized, problematized and, above all, realized in the context of learning workshops and learning workshop work. After a theoretical embedding of the concept of inclusion in the context of learning workshops and the description of possible potentials that learning workshops at universities have for an inclusion-oriented training of future educators, the learning workshop work is framed as an inclusive didactical concept of higher education. In the third chapter of the volume, results from testing and researching inclusive didactics in the context of university learning workshops are presented. From different perspectives, a multifaceted picture of learning workshops in universities as spaces of inclusive pedagogy emerges, in which diversity is welcome and the balance of valuing individuality and community reference can be lived.